Kinerja Terminal Melalui Mediasi Throughput Dermaga di Terminal Petikemas 009 Pelabuhan Tanjung Priok - Imat Rakhmatillah; Lira Agusinta (Institut Transportasi dan Logistik Trisakti, 2019)
The purpose of this research is to find out the effect of ship visits and draught ship with terminal performance by throughput dock. The main problem of this research is about the low of utilization in loading and unloading and box crane hour. This quantitative research used path analysis method. There were 30 respondents from PT Plindo II in container terminal at Tanjung Priok port. The result of the hypothesis on the structure of model -1 showed that the variable of ship visits, draught ship, and throughput dock have positive and significant impact in terminal performance. The structure of model -2 showed that the variable of ship visits and draughput ship have positive and significant impact through terminal performance. On the structure model -2 partially in visit variable and draught ship have positive and significant impact through terminal performance and throghtput dock indirectly. Based on the data, there is positive and significant impact between ship visits, draught ship, and throughput dock of terminal performance in container terminal at Tanjung Priok port.